Crosstalk Effects in Matrix of PZT Sensors for SHM Applications Based on the Electromechanical Impedance Principle - Filho, Jozue Vieira [UNESP]; Cadalso, Mario Rolando Rodriguez [UNESP]; Ledesma, Nicolás Eusebio Cortez; de Oliveira, Mario Anderson; Park, Gyuhae (My University, 2023)
Using PZT transducers leads to different structural health monitoring techniques, such as those based on Frequency Response Function and Lamb Waves. When two or more PZT transducers are closely placed, an important interference, namely crosstalk, appears. This approach verified that such an effect can be modelled and implemented as a technique to detect damage. Accordingly, this work aims to present a methodology for studying the crosstalk effect in arrangements of PZT, where the electromechanical impedance (EMI) is used as a parameter of a PZT arrangement modelled as a coupled transmission line. For that purpose, the eigenvalues of a coupled electromechanical impedance matrix are obtained. We anticipate that the structural damage will influence the EMI signatures and the modelled matrix will be distinct for the healthy and damaged conditions. The proposed methodology was tested by simulating a simple Structural Health Monitoring system based on the EMI technique. The simulated structure was considered as a homogeneous medium in which two small PZT transducers separated by 6mm were attached. Two independent damages were simulated in the structure at 10 mm and 30 mm from each PZT. The initial simulations were implemented using the software SPICE and the crosstalk was estimated in time-domain. Some metric damage indices demonstrated the effectiveness of the proposed methodology.